Viral Zoonoses of National Importance in Ghana: Advancements and Opportunities for Enhancing Capacities for Early Detection and Response - Richard D. Suu-Ire; Evangeline Obodai; J. H. Kofi Bonney; Samuel O. Bel-Nono; William Ampofo; Terra R. Kelly (Journal of Tropical Medicine)
Zoonotic diseases have devastating impacts on human and animal health, livelihoods, and economies. Addressing the complex web of interrelated factors leading to zoonotic disease emergence and spread requires a transdisciplinary, cross-sectoral approach, One Health. The One Health approach, which considers the linkages between the health of people, animals, and their shared environment, presents opportunities to reduce these impacts through a more holistic coordinated strategy to understanding and mitigating disease risks. Understanding the linkages between animal, human, and environmental health risks and outcomes is critical for developing early detection systems and risk reduction strategies to address known and novel zoonotic disease threats. Nearly 70 countries across the world, including Ghana, have signed on to the Global Health Security Agenda (GHSA), which is facilitating multisectoral approaches to strengthen country capacities in the prevention and early detection of and respond to infectious disease threats. Currently, Ghana has not yet formalized a national One Health policy. The lack of a clearly defined multisectoral platform and limited collaboration among key Ghanaian Ministries, Departments, and Agencies has impacted the country’s ability to effectively mitigate and respond to emerging and reemerging zoonoses. Many of these emerging zoonoses are caused by viruses, which, because of their diversity and evolutionary properties, are perceived to pose the greatest threat to global health security. Here, we review viral zoonoses of national importance and priority in Ghana, highlight recent advancements in One Health capacities, and discuss opportunities for implementing One Health approaches to mitigate zoonotic disease threats.